Non-linear elliptic equation in conformal geometry - Chang, Sun-Yung Alice (European Mathematical Society, 2004)
Non-linear elliptic partial differential equations are an important tool in the study of Riemannian metrics in differential geometry, in particular for problems concerning the conformal change of metrics in Riemannian geometry.